CA‐S27: A novel Lewis a associated carbohydrate epitope is diagnostic and prognostic for cholangiocarcinoma - Silsirivanit, Atit (Cancer Sci, 2013)
Early and specific diagnosis is critical for treatment of cholangiocarcinoma (CCA). In this study, a carbohydrate antigen‐S27 (CA‐S27) monoclonal antibody (mAb) was established using pooled CCA tissue‐extract as immunogen. The epitope recognized by CA‐S27‐mAb was a new Lewis‐a (Le(a)) associated modification of MUC5AC mucin. A Soybean agglutinin/CA‐S27‐mAb sandwich ELISA to determine CA‐S27 in serum was successfully developed. High level of CA‐S27 was detected in serum of CCA patients and could differentiate CCA patients from those of gastro‐intestinal cancers, hepatomas, benign hepatobiliary diseases and healthy subjects with high sensitivity (87.5%) and high negative predictive value (90.4%). The level of serum CA‐S27 was dramatically reduced after tumor removal, indicating tumor origin of CA‐S27. Patients with high serum CA‐S27 had significantly shorter survivals than those with low serum CA‐S27 regardless of serum MUC5AC levels. Fucosyltransferase‐III (FUT3) was shown to be a regulator of CA‐S27 expression. Suppression of CA‐S27 expression with siRNA‐FUT3 or neutralization with CA‐S27 mAb significantly reduced growth, adhesion, invasion and migration potentials of CCA cells in vitro. In summary, we demonstrate that serum CA‐S27, a novel carbohydrate antigen, has potential as diagnostic and prognostic markers for CCA patients. CA‐S27 involves in promoting cell growth, adhesion, migration and invasion of CCA cells.